Analysis of the Need for Development of Website-Based Physical Education Learning Media for Elementary Schools - Dwi Yayang Fahrina; Syafaruddin Syafaruddin; Iyakrus Iyakrus; Meirizal Usra; Wahyu Indra Bayu; Herri Yusfi (UNIVERSITAS NEGERI MAKASSAR, 2023)
This research aims to analyze the need for developing website-based Physical Education learning media for elementary schools. This type of research is research and development (R&D). This population is elementary school students at SD Negeri 18 Palembang who are in fifth grade. The sample used on a small scale was twenty-seven students and for a large scale it was sixty students. The instrument in this research is data collection using questionnaires and the results of students' Google forms. The data analysis technique used is a description of the questionnaire data that has been filled in by the respondent. Based on the research results, it was found that almost (62.2%) of the respondents knew about web-based physical education learning media in elementary schools and only 37.8% did not know about it. As many as 98.9% chose to require WEB-based learning, only 1.1% chose not. 58.9% of respondents experienced difficulties with the current learning media and only 41.1% of respondents said that WEB-based learning media for elementary school children was not only 1.1% and 40% chose it as important while 58% chose it as very important. 9% and those who did not agree that web-based physical education learning media was developed were only 2.2%, while those who agreed were 41.1% and 56.7% strongly agreed. Research on the development of website-based physical education learning media can be used well by students and is useful as learning material at the moment